Intrinsic and induced quantum quenches for enhancing qubit-based quantum noise spectroscopy - Yu-Xin Wang (Nature Portfolio, 2021)
When trying to characterise a bath coupled to a sensor qubit, one should consider that quantum environments change their properties in response to external perturbations. Here, the authors show how back-action of the qubit on the bath leads to a quench, which can be used to infer the bath spectral function.